Analysis Of Health Equity And Access Of Healthcare In Indonesia - Putri Rahayu, Eka; Ariyanti, Rea; Putri Rahayu, Agustin (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Health care systems around the world implement policies and interventions to improve access to health care for marginalized populations. Health care organizations must consider equitable access to care, regardless of factors such as gender, socioeconomic status, ethnicity or disability. Timely access to quality care is a fundamental ethical principle. By promoting equitable distribution of resources, health care organizations can reduce disparities and provide a fair opportunity for all individuals to receive needed health care (Lelyana, 2023). Public health policies should ensure equality of access to health services and equity in the distribution of health resources. This involves identifying and addressing health disparities that may arise from social, economic or demographic factors (Indarwati et al, 2024 ). Health equity is fundamental to the idea of living a good life and building a vibrant society because of its practical, economic, and civic implications. Shifts in economic mobility, income inequality, and persisting legacies of social problems such as structural racism are hampering the attainment of health equity, causing economic loss, and most overwhelmingly, the loss of human lives and potential (Weinstein et al, 2017). Health equity is the state in which everyone has the opportunity to attain full health potential and no one is disadvantages from achieving this potential because of social position or any other socially defined circumstances. Health equity and opportunity are inextricably linked. (Weinstein et al, 2017) The committee took a multifactor view of health status and health inequities, in recognition that only some aspects of a person’s health status depend on individual behaviors and choice. Community-wide problem, such as poverty, unemployement, low educational attainment, inadequate housing, lack of public transportation, exposure to violence, and neighborhood deterioration (social or physical) shape health and contribute to health inequalities (Weinstein et al, 2017). To truly eliminate health disparities and thereby achieve health equity, many solutions require a social justice lens (Smalley et al, 2021). Meanwhile, health equality is the achievement of the highest level of health for all people. To achieve this health equality, everyone needs to respect social equality (Siregar dan Rahman, 2022). Indonesia is an archipelagic country consisting of 17,374 islands, with an area of 1,892,410.1 km2. The large number of islands in Indonesia with various tribes, cultures and languages poses its own challenges in the government's efforts to provide health services for the Indonesian people (Ministry of Health, 2024). The level of public health in a country can be influenced by the existence of health service facilities. Health service facilities are entities that deal directly with the community. Primary Health Care and hospitals are still the main types of health services that provide basic and referral health services. The number of Primary Health Care in Indonesia in 2023 will be 10,180 Primary Health Care, consisting of 4,210 inpatient health centers and 5,970 non-inpatient health centers. The number of hospitals in Indonesia in 2023 will be 3,155, consisting of 2,636 general hospitals and 519 special hospitals. The number of posyandu in Indonesia in 2023 will be 304,263 posyandu spread throughout the region (Ministry of Health, 2024). The large number of health facilities available raises the question of whether they are able to provide the best medical services and can be accessed by all levels of society Based on the description above, it needs to be analyzed health equity and access of healthcare in Indonesia. Objective : This article provide a review of the analysis health equity and access of healthcare in Indonesia. previous research or taking secondary data from various sources. Research Methods/ Implementation Methods : Results : This study used the Retrospective Observational method with a qualitative approach in conducting a Systematic Review to combine findings from qualitative descriptive studies. The study uses internal data sources to identify and assess scientific publications to find reliable and accurate references. The author conducted a search using Google Scholar with the keywords “access and equity healthcare” to evaluate how healthcare facilitate the society to access healthcare services. This study uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, following the right steps and procedures to synthesize the results of descriptive qualitative research. The survey was conducted using mobile phones, laptops, prepaid operator networks and wi-fi. These tools were used to search for content, especially research journals that are relevant to the subject of this study. This study examines how social and economic inequalities affect communities' access to safe and affordable healthcare services. This research was conducted by conducting a survey using information gathering methods involving various techniques, including systematic reviews and literature searches. After data extraction and synthesis, a final report will be prepared in which the results will be assessed qualitatively and the collected research material will be critically analyzed in the context of the study. It is stated that the main factors influencing the ability of rural communities to utilize primary health services are geographic access, economic and social. Patients hope that the hospital can be easily reached using public transportation or private vehicles. Apart from that, patients also hope that the roads around the hospital will not be hampered by traffic jams JKN program has succeeded in significantly increasing access to health services for the community, further efforts are still needed to improve the quality and effectiveness of these services, as well as to overcome various obstacles faced in their implementation Conclusion/Lesson Learned : The number of hospitals and health centers increases from year to year. Equality and access to health services in Indonesia requires improvement from various aspects. It is recommended to improve transport infrastructure, increasing access to health services by telemedicine, increase public awareness of the importance of getting trusted and easily accessible health services.